Marketing Strategies and Their Application in Small and Medium Enterprises Emphasizing the Modern Methods (Vallis Aurea, 2016)
This paper will be focused on marketing strategies and their application in SMEs. Application of marketing today has become almost mandatory and the need for implementation of a common strategy. The marketing elements and strategies to invest more and more and business and other entities allocate an increasing proportion of its funds administration with a view to later less uncertain business. Marketing and its strategy is possible, and should be implemented in almost any aspect of a subject. If it does not comply with the above instruction, often in question leads itself existence same entity because who does not progress, ie. who is stagnating, in fact, going backwards, because the competition is not standing still. The competition is more ruthless, especially nowadays. The reason for this is the increasing power of buyers or consumers who have an increasing role in defining a product or service. One of the reasons is also the opening of borders, cheaper transportation, labor costs, etc. All of this points to the need for separation from dozens of new ideas, products, services, etc. Any strategy including the implementation of the marketing strategy should be preceded by thorough market research and situation in general. A number of entities, institutions and others neglect this very important step because of unwarranted fear of spending scarce resources, which actually unwittingly placed in a even worse situation, implementing some strategies which later often results in failure and even higher additional costs.